High-Pressure Adsorption Isotherms of Carbon Dioxide and Methane on Activated Carbon From Low-Grade Coal of Indonesia. Issue 4 (4th March 2017) - Martin, Awaludin; Idrus Alhamid, Muhammad; Nasruddin,; Suryawan, Bambang; Soong Loh, Wai; Bin Ismail, Azhar; Chun, Wongee; Choon Ng, Kim
ABSTRACT: Adsorption isotherms data of methane and carbon dioxide gases on the activated carbons were measured experimentally using a volumetric method with pressure and temperatures ranging from 0 to 3.5 MPa and 27 to 65°C, respectively. Two types of activated carbons, namely, (1) Kalimantan Timur type activated carbon, which is lab-produced from Indonesian low-grade coal and (2) a commercial (Carbotech) activated carbon were used. The adsorption isotherms obtained were found to belong to type 1 of the International Union of Pure and Applied Chemistry classification. The adsorption uptakes for both carbon dioxide and methane on commercial activated carbon are higher than for the Kalimantan Timur activated carbon. This is due to higher Brunauer–Emmet–Teller surface area and pore volume of the former. Langmuir and Tóth isotherm models are correlated to predict the experimental data with acceptable accuracy.